Evaluation of a new method for (L+) lactic acid purification, using ethyl ether - Coelho, Luciana Fontes [UNESP]; Sass, Daiane Cristina [UNESP]; Avila Neto, Paulo Marcelo [UNESP]; Contiero, Jonas [UNESP] (Elsevier, 2020)
The aim of the present study was to obtain high levels of fermentative L (+) lactic acid and find a better form of purification. The process was optimized by testing different compositions of the culture media, evaluating alternative carbon and nitrogen sources (agribusiness waste products), using inexpensive procedures and improve the production, recovery and purification of lactic acid from the fermented broth. Using 100 g/L crystallized sugar, 30 g/L yeast autolysate and NH4OH as the neutralizing agent, the production of L (+) lactic acid by Bacillus coagulans arr4 was 75.26 g/L in 24 h, with 2.76 g/L of residual sugar. The lactic acid purification and recovery experiments using double filtration with charcoal and Celite followed by a cation exchange column led to the economic recovery of lactic acid and the removal of substances and sugars. However, an additional purification step (extraction with ethyl ether) was needed for a microwave lactic acid polymerization reaction. Average recovery was 80%, with high purity.
Keywords: Bacillus; Celite; Charcoal; Ethyl ether; Lactic acid; Purification